Effect of sintering temperature on microstructures and mechanical properties of ZK60 magnesium alloys. (14th January 2022) - Ma, Luosheng; Ma, Lili; Jin, Peipeng; Feng, Xinya; Jia, Lei
Abstract: In this study, ZK60 Mg alloys were prepared via hot-press sintering under a constant pressure of 30 MPa as well as Ar atmosphere. The sintering temperature was determined to be in the range of 450 °C–600 °C with an interval of 50 °C. The effect of sintering temperature on the microstructures and mechanical properties of the alloys was investigated. All the four sintered alloys mainly exhibited an α -Mg-phase structure and equiaxed grain microstructure. However, a specific amount of melt, enriched in Zn element, formed when the sintering temperature reached 500 °C. Thus, only the alloy sintered at 450 °C maintained the nominal composition of the alloy powder, and exhibited the favorable yield strength and hardness, which was 135.1 MPa and 57 HV, respectively. The alloys sintered at 550 °C and 600 °C exhibited a reduced yield strength and hardness due to the loss of Zn element.